Mind Over Matter in the Philippines : A Study of Key Stakeholders' Perceptions of Childhood Stunting - Sen, Iman; Mbuya, Nkosinathi; Demombynes, Gabriel; Gauri, Varun (World Bank, Washington, DC, 2020)
Declines in rates of child stunting in the Philippines have decelerated, making it hard for the country to achieve its targets on nutritional outcomes. The knowledge base, beliefs, and practices of caregivers have been extensively researched, but little is known about how health workers and policy makers fare in comparison. The authors conduct qualitative interviews, striving to preclude bias as we capture these stakeholders’ views on factors that affect stunting, and go on to compare and contrast these perceptions. The authors subsequently investigate the importance of the different factors in detail through a large-scale quantitative survey with frontline health and nutrition workers. The findings suggest that while most workers’ knowledge and beliefs are consistent with accepted practices, important deviations from consensus views exist, and these are correlated with worse self-reported service delivery outcomes at local health centers. The findings suggest that in the Philippines any endeavor to further improve service delivery must take into consideration the beliefs of frontline workers.